High-Intensity Interval Training: Methodological Considerations for Interpreting Results and Conducting Research - Andreato L.V.* (2020)
© 2020 Elsevier LtdIn recent years, high-intensity interval training (HIIT) has gained prominence in the health and fitness area, becoming a worldwide trend. Given the positive results of HIIT, researchers have compared it with moderate-intensity continuous training (MICT). However, much of that research has presented methodological challenges. Therefore, the aim of this opinion article is to address an important risk of bias common in research comparing HIIT and MICT: the lack of equalisation among protocols. This limitation can be considered a risk of bias that limits the conclusions of many studies. Thus, it is necessary to achieve the equalisation of sessions in some way such as using equalisation by energy expenditure, by workload performed in the session, or by duration of the session.